Effect of Low-Level Laser Therapy on Osseointegration: A Comprehensive Review - Adaki, Raghavendra; Adaki, Shridevi; Karagir, Amol; Agrawal, Jivanasha (Journal of Neonatal Surgery, 2025)
Low-Level Laser Therapy (LLLT), also known as photobiomodulation, has garnered attention in the field of implant dentistry for its potential to enhance osseointegration—the direct structural and functional connection between living bone and the surface of a load-bearing implant. This review aims to critically evaluate the current evidence on the efficacy of LLLT in promoting bone regeneration and improving the integration of dental implants with surrounding bone tissue. By analysing both preclinical and clinical studies, we seek to elucidate the underlying mechanisms of LLLT and its practical applications in enhancing implant success rates.